The Target Material Influence on the Current Pulse during High Power Pulsed Magnetron Sputtering - Moens, Filip; Konstantinidis, Stéphanos; Depla, Diederik (Frontiers in Physics, 2017)
The current-time characteristic during high power pulsed magnetron sputtering is measured under identical conditions for seventeen different target materials. Based on physical processes such as gas rarefaction, ion-induced electron emission, and electron impact ionization, two test parameters were derived that significantly correlate with specific features of the current-time characteristic: i) the peak current is correlated to the momentum transfer between the sputtered material and the argon gas, ii) while the observed current plateau after the peak is connected to the metal ionization rate.